The Antimicrobial and Antioxidant Effects of Equisetum arvense Extracts - Eren, Ayşe; İnci, Şule; Kırbag, Sevda (My University, 2024)
Equisetum arvense L, also known as horsetail, is a medicinal plant used in traditional medicine. Especially, it is used in the treatment of bleeding, antiseptic, anti-inflammatory, urethritis, jaundice and hepatitis. In the study, the antimicrobial and antioxidant activities of extracts obtained from different solvents of E. arvense were investigated. Antimicrobial activity of E. arvense extracts was determined using the disc diffusion method. The antimicrobial activity was determined utilizing the pathogenic microorganisms Staphylococcus aureus, Klebsiella pneumoniae, Escherichia coli, Bacillus megaterium, Candida albicans and Candida glabrata. In the results obtained, it was determined that the ethanol extract of E. arvense at 500 µg concentration showed antimicrobial activity at different rates (14.3-28.0). Ethanol extract showed the highest antimicrobial activity against Candida glabrata (28.0 mm) at the same concentration. It was detected that the chloroform extract showed antimicrobial activity (7.3-10.6 mm) against the microorganisms used. The antioxidant activity of the aerial parts of E. arvense at different concentrations of methanol extract was determined according to the 2,2-diphenyl-1-picrylhydrazil radical scavenging capacity method. The highest radical scavenging capacity of the methanol extract was observed at a concentration of 10mg/mL (91.5%). The IC50 value of the methanol extract of E. arvense was calculated as 3.13 mg/mL.
Keywords: Antioxidant; antimicrobial; medicinal plant; Equisteum arvense